Multiobjective reliability-based design optimization of structural dynamical systems under stochastic excitation - Jerez, Danko J.; Jensen, Hector A.; Chen, Jianbing (Mechanical systems and signal processing, 2024)
This contribution presents a framework to address multiobjective reliability-based design optimization problems involving structural dynamical systems under stochastic excitation. In particular, it is assumed that first-passage probabilities are incorporated in the definition of some of the objective functions. Instead of trying to characterize the entire Pareto front, the focus is on exploring the vicinity of specific tradeoff solutions in an effective manner. To this end, a compromise programming problem is formulated using a weighted Chebyshev metric based on aspiration levels, which is then solved by means of a two-phase stochastic search technique that sequentially explores the corresponding feasible and optimum solution sets. A number of nearly equivalent tradeoff designs are obtained at the end of the solution process, which provides insight and flexibility for decision-making purposes. For enhanced numerical efficiency, the associated reliability measures are estimated using an adaptive surrogate model strategy. An application problem involving a four-story nonlinear building subject to stochastic ground excitation is presented. Numerical results suggest that the proposed framework can be regarded as an effective tool to determine tradeoff solutions in a practical class of engineering design problems. •Compromise programming method is integrated with a stochastic search technique.•Framework allows generating a set of nearly equivalent compromise designs.•Nontrivial information for decision making can be obtained.•Effective technique to address a practical class of structural design problems.